THE CORRELATION BETWEEN STUDENTS’ SCANNING TECHNIQUE AND THEIR READING COMPREHENSION ON REPORT TEXT - Nurdiana, Nurdiana; Afrizal, Afrizal; Utami, Cleofatra (State Islamic University of Sultan Syarif Kasim Riau, 2025)
This research was to investigate the significant correlation between students’ scanning technique and their reading comprehension. The design of this research was quantitative research. The total number of population was 120 students which consisted of 4 classes. The researchers took 30 students in one class by using random sampling as the technique for choosing the sample.. In collecting data, researchers used scanning tests and reading comprehension tests. For analyzing the data, researchers used descriptive statistics, simple linear regression analysis and the Pearson product moment correlation formula. Data were analyzed using the SPSS program. Based on the research results, it is known that the average score for scanning techniques is 75.00. while the average students’ reading comprehension score was 80.00. By using simple linear regression analysis via SPSS 23.0, researchers found that there was a low relationship between students' scanning technique and reading comprehension of report text. The categorized as moderate correlation with a coefficient of 0.481.